Teachers’ Perspectives on the Need for Integrating Guidance and Counseling Services in Schools - Damanik, Cristin Mutiara; Budi Astuti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The integration of Guidance and Counseling (BK) services at SMP Negeri 1 Bagan Sinembah, Riau, has not been implemented in accordance with the provisions of Law Number 20 of 2003 on the National Education System. This study aims to evaluate teachers' perceptions of the need for integrating BK services. The research method employed is a quantitative approach, utilizing a survey that involved 35 teachers as respondents. The results show that the majority of respondents (31.43%) fall into the "Moderate" category regarding the need for BK services, followed by the "Low" and "High" categories, each at 25.71%. Data analysis using correlation tests indicates a positive relationship between perspective and teaching experience, with a correlation coefficient of 0.290 (p < 0.05), suggesting that the higher the teaching experience, the more positive the perspective on the importance of BK services. The conclusions of this study can provide valuable insights for education policymakers, highlighting the importance of increasing teacher awareness through regular training and workshops, as well as collaborating with guidance and counseling professionals to integrate guidance and counseling services at SMP Negeri 1 Bagan Sinembah. Keywords: integration of guidance and counseling services, teachers’ perspectives, need for guidance and counseling services